Internal Control Systems And Financial Accountability In Public Sector Enterprises - Alvianita Gunawan Putri; Musyafa Al Farizi; Novitasari Eviyanti; Bagus Yunianto Wibowo; Destine Fajar Wiedayanti (LP2M IAIN Palopo, 2025)
Main Purpose - This study aims to evaluate the effectiveness of the Internal Control System (ICS) in improving financial accountability, transparency, and operational efficiency in regional public enterprises. Method - The methodology used is a qualitative approach, combining interviews with key stakeholders and a systematic literature review (SLR) to assess the implementation of ICS and its impact on financial management. Main Findings - The results show that well-implemented ICS significantly contributes to improving financial accountability and transparency, as well as reducing the risk of public funds being misused. However, challenges were identified in implementing ICS, including a lack of staff training, inadequate technological infrastructure, and discrepancies between the planned budget and actual expenditures. Theory and Practical Implications - This study recommends strengthening staff training, enhancing technological infrastructure, and reinforcing internal control procedures to ensure optimal implementation of ICS. These steps are expected to improve financial governance in the public sector. Novelty - The novelty of this research lies in the approach that combines interviews with stakeholders and systematic literature review (SLR) to evaluate the implementation of the Internal Control System (SPI) in regional public companies, as well as identifying the challenges faced and providing recommendations to strengthen SPI in improving accountability and financial transparency in the public sector.